ANALISIS KONTRIBUSI PAJAK KENDERAAN BERMOTOR (PKB) TERHADAP PENDAPATAN ASLI DAERAH (PAD) DI PROVINSI SUMATERA UTARA - Sari Bulan Tambunan (JURNAL AKUNTANSI DAN BISNIS : Jurnal Program Studi Akuntansi, 2016)
Motor Vehicle Tax (PKB) is one source of revenue Daerahyang make a significant contribution to the financing of regional governance and development in the province of North Sumatra. The Motor Vehicle Tax is one of the Provincial Tax regulated in Law Number 34 Year 2000 regarding amendments to the Law of the Republic of Indonesia Number 18 Year 1997 on Regional Taxes and Levies. This study uses empirical juridical approach. In the data collection and baham both primary and secondary law. The problems that were collected through interviews and a study of the documents that exist in the Department of Revenue in North Sumatra Province. While the technique of analysis was done descriptively qualitative.Motor Vehicle Tax (PKB) levied by the North Sumatra Provincial Regulation No. 3 of 2002 and the Motor Vehicle Tax Implementation Regulations based on Law No.34 of 2000 on the implementation of the PKB collection has been run in accordance with the legislation in force despite some technical obstacles in the implementation of the collection as well as its contribution to the regional revenue in the province of North Sumatra. The existence of these barriers by samsat in North Sumatra province has made efforts to overcome the obstacles that arise.